The market varieties replenishment: soybean (Glycine max. (L.) Merrill.) - О. І. Безручко; О. В. Колесніченко; Т. М. Лазоренко (Plant Varieties Studying and Protection)
The article concerns directions of valuable protein crops using, soybeans, growth rates of its production throughout the world in recent years, the opportunity and the necessity of making this crop strategic in our country, problems and prospects of the high-grade soybeans resources formation, the full characteristic of new soybean varieties listed in the State register of Plant Varieties suitable for distribution in Ukraine in 2013.